2017
DOI: 10.1111/anae.13745
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular oxygen sensors with novel applications for bedside respiratory monitoring

Abstract: SummaryMeasurement allows us to quantify various parameters and variables in natural systems. In addition, by measuring the effect by which a perturbation of one part of the system influences the system as a whole, insights into the functional mechanisms of the system can be inferred. Clinical monitoring has a different role to that of scientific measurement. Monitoring describes measurements whose prime purpose is not to give insights into underlying mechanisms, but to provide information to ‘warn’ of imminen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…We conclude that the mechanism determining these respiratory PaO 2 oscillations is the variation of alveolar oxygen tension within the breath, with oxygen entering the alveoli during each inspiration, and that these cyclic variations in alveolar oxygen tension are transmitted all the way to the systemic arteries. Our results in an anaesthetized, ventilated pig model, in the absence of lung injury, may have implications for the interpretation of the results from conditions of lung disease 33 , in particular from patients with lung injury, and from animal models of ARDS.…”
Section: Discussionmentioning
confidence: 78%
“…We conclude that the mechanism determining these respiratory PaO 2 oscillations is the variation of alveolar oxygen tension within the breath, with oxygen entering the alveoli during each inspiration, and that these cyclic variations in alveolar oxygen tension are transmitted all the way to the systemic arteries. Our results in an anaesthetized, ventilated pig model, in the absence of lung injury, may have implications for the interpretation of the results from conditions of lung disease 33 , in particular from patients with lung injury, and from animal models of ARDS.…”
Section: Discussionmentioning
confidence: 78%
“…In [60], they reported a preliminary dynamic sensing device with the potential to change the way clinicians understand disordered gas exchange in patients with lung injury, based on rapid PaO 2 sensing by a plastic optical fiber sensor capable of being inserted into a standard arterial cannula. The authors also reported the potential to detect an excessive pressure or distension of already aerated lung impairments to blood flow to the 'ideal alveolus', allowing better-informed choices of PEEP (positive end-expiratory pressure), respiratory rate, and inspiratory/expiratory (I:E) ratio.…”
Section: Sensors In Healthcare Home Medical Assistance and Continuomentioning
confidence: 99%
“…These probes can be used to visualize within-breath oscillations of paO 2 . Current research proposes to use the information gained from dynamic monitoring to tailor ventilator settings according to the individual patients’ conditions ( Formenti and Farmery, 2017 ).…”
Section: Assessing Oxygen Sensing In Vitro and mentioning
confidence: 99%